Analysis of the Quality of Pantalon Stitching Results Using the Pattern on Fabric Technique for Short Fat Women at Rencong Tailors - Laura; Dermawan; Dilla; Farihah (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
The purpose of this study is to determine the quality of sewing results of women's plus-size pantaloon, using the pattern-on-fabric technique at Rencong Tailor in Binjai. This study consists of one variable, and the researchers employed a descriptive research method. The population of this study included plus-size women with a waist circumference of 100-105 cm and a hip circumference of 120-125 cm. The objects used in this study were 5 pairs of plus-size pantaloon that were sewn using the pattern-on-fabric technique at Rencong Tailor in Binjai. Data collection was carried out using observation sheets with the help of 5 observers, consisting of 3 lecturers in Fashion Design and Clothing and 2 experts in pantaloon making. Based on the calculation results from the observation assessments, the researchers found that the sewing results of plus-size short pants using the pattern-on-fabric technique obtained the highest score of 98 and the lowest score of 89. The average value (Mean) was 94.2, and the standard deviation was 69.06 for each indicator.